Optical superoscillation technologies beyond the diffraction limit - Zheludev, Nikolay I. (2022)
Optical superoscillations are rapid, subwavelength spatial variations of the intensity and phase of light, occurring in complex electromagnetic fields formed by the interference of several coherent waves. The discovery of superoscillations stimulated a revision of the limits of classical electromagnetism — in particular, the studies of phenomena such as unlimitedly small energy hotspots, phase singularities, energy backflow, anomalously high wavevectors and their intriguing similarities to the evanescent plasmonic fields on metals. In recent years, the understanding of superoscillatory light has led to the development of superoscillatory lensing, imaging and metrology technologies. Dielectric, metallic and metamaterial nanostructured superoscillatory lenses have been introduced that are able to create hotspots smaller than allowed by conventional lenses. Far-field, label-free, non-intrusive deeply subwavelength super-resolution imaging and metrology techniques that exploit high light localization and rapid variation of phase in superoscillatory fields have also been developed, including new approaches based on artificial intelligence. We review the fundamental properties of superoscillatory optical fields and examine emerging technological applications.